Social Exchange Theory: An Interdisciplinary Review - Cropanzano, Russell; Mitchell, Marie S. (Journal of Management, 2005)
Social exchange theory (SET) is one the most influential conceptual paradigms in organizational behavior. Despite its usefulness, theoretical ambiguities within SET remain. As a consequence, tests of the model, as well as its applications, tend to rely on an incompletely specified set of ideas. The authors address conceptual difficulties and highlight areas in need of additional research. In so doing, they pay special attention to four issues: (a) the roots of the conceptual ambiguities, (b) norms and rules of exchange, (c) nature of the resources being exchanged, and (d) social exchange relationships.